2013
DOI: 10.1007/s13197-013-1059-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and pancreatic α-amylase inhibitory activity of isolated fractions from water extract of Qingzhuan tea

Abstract: In the present work, Qingzhuan tea, a unique dark tea produced by post-fermentation technology, was selected to investigate its antioxidant and pancreatic α-amylase inhibiting activities. Water extract of Qingzhuan tea was successively isolated by solvent partitioning procedures to obtain chloroform, ethyl acetate, n-butanol, sediment and residual aqua fractions. Of different fractions, the ethyl acetate fraction (QEF) had the highest total polyphenols and catechins contents, demonstrated the strongest DPPH ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Comparatively, subfractions F2–F10 from BSF of CoTE showed better DPPH free radical scavenging activity (IC 50 < 71.2 µg mL −1 ) than the subfractions of the A. confusa bark extract. Cheng et al reported the ethyl acetate soluble fraction of Qingzhuan tea was separated into eight subfractions by Sephadex LH‐20 gel chromatography, and the DPPH free radical scavenging and α‐amylase inhibitory activities increased from subfractions F1 to F8. The IC 50 values of DPPH free radical scavenging and α‐amylase inhibitory activities of subfraction F8 were 4.6 µg mL −1 and 0.4 mg mL −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Comparatively, subfractions F2–F10 from BSF of CoTE showed better DPPH free radical scavenging activity (IC 50 < 71.2 µg mL −1 ) than the subfractions of the A. confusa bark extract. Cheng et al reported the ethyl acetate soluble fraction of Qingzhuan tea was separated into eight subfractions by Sephadex LH‐20 gel chromatography, and the DPPH free radical scavenging and α‐amylase inhibitory activities increased from subfractions F1 to F8. The IC 50 values of DPPH free radical scavenging and α‐amylase inhibitory activities of subfraction F8 were 4.6 µg mL −1 and 0.4 mg mL −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…; Cheng et al . ). While ABTS is another organic free radical and is more versatile than DPPH due to its application of assessing the scavenging capacity for both polar and nonpolar samples (Basha and Priscilla ; Shang et al .…”
Section: Resultsmentioning
confidence: 97%
“…Cheng et al . () also found that water extract from Qingzhuan tea exhibited a dose‐dependent inhibitory effect against pancreatic α‐amylase activity. As the main catechin monomers of TP, nongalloylated catechins and galloylated catechins were found to act as the natural inhibitors of human α‐amylase.…”
Section: Introductionmentioning
confidence: 88%